Association Between Preadmission Metformin Use and Outcomes in Intensive Care Unit Patients With Sepsis and Type 2 Diabetes: A Cohort Study - Yang, Qilin; Zheng, Jiezhao; Chen, Weiyan; Chen, Xiaohua; Wen, Deliang; Chen, Weixiao; Xiong, Xuming; Zhang, Zhenhui (Frontiers in Medicine, 2021)
Background: Sepsis is a deadly disease worldwide. Effective treatment strategy of sepsis remains limited. The association of preadmission metformin exposure and mortality in sepsis patients with diabetes are still controversial. We aimed to assess sepsis-related mortality in patients with type 2 diabetes (T2DM)who were preadmission metformin and non-metformin users . Methods: We included patients with sepsis and T2DM in Medical Information Mart for Intensive Care -III database. Outcome was 30-day mortality. Adjusted hazard ratio (HR) with 95% CI were calculated in multivariable Cox regression analyses in this cohort. Results: We included 2,383 sepsis patients with T2DM (476 and 1,907 patients were preadmission metformin and non-metformin uses) between 2001 and 2012. The overall 30-day mortality was 20.1% (480/2,383); it was 21.9% (418/1,907) and 13.0% (62/476) for non-metformin and metformin users, respectively. After adjusted for age, sex, ethnicity, marital status, insurance, admission type, service unit, heart rate, mean arterial pressure (MAP), respiratory rate, SPO2, white blood cell count, creatinine, hemoglobin, platelet, ventilator use, vasopressor use, comorbidity disease, simplified acute physiology score (SAPS) II score, glucose, RRT use, tested HBA1C, infection site, insulin, aspirin and statin, we found that preadmission metformin use was associated with 39% lower of 30-day mortality (HR=0.61, 95% CI:0.46-0.81, p=0.007). In sensitivity analyses, subgroups analyses, and propensity score matching, the results remain stable. Conclusions: Preadmission metformin use may be associated with reduced risk-adjusted mortality in patients with sepsis and T2DM. This association warrants further investigation.